Detection of specific antibodies to Neospora caninum and Toxoplasma gondii in naturally infected alpacas (Lama pacos), llamas (Lama glama) and vicuñas (Lama vicugna) from Peru and Germany - Wolf, Dennis (2005)
Sera of an experimentally Neospora caninum infected llama and a non-infected control llama were used to establish an immunoblot, an ELISA and an IFAT to detect antibodies against N. caninum tachyzoites. Subsequently, serum samples collected from a total of 871 South American Camelids (SAC: Lama glama, Lama pacos, Lama vicugna) of two farms in Peru and from 32 SAC of a farm in central Germany were examined for antibodies against N. caninum and Toxoplasma gondii. Based on the recognition of specific bands in the immunoblot, sera of SAC from Peru were differentiated into N. caninum-positive (n = 18) and T. gondii-positive (n = 30) samples and into samples negative or inconclusive for both parasites. Using the immunoblot results as the reference, a modified version of the p38-ELISA and the IFAT were evaluated for detecting N. caninum antibodies in SAC sera. Applying a cut-off as determined by two graph-receiver operating characteristic analysis both, the ELISA and the IFAT, exhibited a sensitivity and specificity of about 95% in the SAC sera from Peru. Serological testing confirmed that SAC may become infected with N. caninum under field conditions in Peru. In addition to alpacas and llamas also 114 wild living vicuñas had been examined for antibodies against N. caninum. However, only the alpacas and llamas but no vicuñas were found N. caninum-positive. In contrast, T. gondii-seropositive animals were detected in all three SAC species. The lack of N. caninum-seropositive vicuñas indicates that in the study area in Peru wild canids might not serve as definitive hosts of N. caninum while for T. gondii a life cycle including wild felids is likely. On the German farm no N. caninum- but only T. gondii-seropositive SAC (n = 14) were detected. The seroprevalence of T. gondii infection was significantly higher in adult SAC (alpacas in Peru, llamas in Germany) than in crias (i.e. <12 months old foals) indicating that the predominant route of infection is post natal. Since the present study was restricted to a few farms, the seroprevalences determined are not representative. However, our results confirm natural infections with N. caninum and T. gondii in SAC. Whether these infections are linked to any disease, e.g. reproductive losses, has to be clarified in further studies.